Piracy and intellectual property in Latin America rethinking creativity and the common good - Goldgel Carballo, Víctor 1978-; Poblete, Juan 1962- (Routledge, 2020)
"Piracy and Intellectual Property in Latin America is the first sustained effort to present an alternative framework for understanding piracy and contemporary challenges to global discourses on intellectual property in the Americas. While piracy might just look like theft and derivative reproduction from the perspective of many right-holders, the contributors to this volume go beyond this economic-driven logic and show how practices of copying are in fact practices of reinvention which reflect the rich social networks and forms of creativity, authorship, commerce, and consumption that characterize informal economies. From a perspective informed by contemporary scenarios in Mexico, Brazil, Chile, Argentina, Peru, Guatemala, and the United States, they engage in a discussion of alternatives that-predicated on the importance of protecting culture-allow for other ways of conceiving prosperity at local, national, regional, and global levels. Examples discussed include video games, clothing, trinkets, music, film, TV, and books. Designed to help understand the broader implications of IP and piracy for the field of Latin American Studies, this book will be a major contribution to Global South studies, as well as to the growing bibliography on globalization, informal markets, and piracy"--
2004
Keywords: Piracy (Copyright) / Latin America; Piracy (Copyright); Latin America